Dual-functional bacterial cellulose modified with phase-transitioned proteins and gold nanorods combining antifouling and photothermal bactericidal properties. (30th May 2022) - Li, Luohuizi; Li, Guize; Wu, Yong; Lin, Yuancheng; Qu, Yangcui; Wu, Yan; Lu, Kunyan; Zou, Yi; Chen, Hong; Yu, Qian; Zhang, Yanxia
Highlights: A facile method is developed for endowing bacterial cellulose (BC) with antifouling and photothermal antibacterial properties. The modified BC is fabricated by physical incorporation of gold nanorods followed by deposition of a phase-transitioned protein film. The modified BC can suppress bacterial adhesion and kill the bacteria that broke through the antifouling layer under NIR irradiation. The modified BC exhibits negligible cytotoxicity in vitro and good histocompatibility in vivo . Abstract: Bacterial cellulose (BC) is one of the most versatile natural biopolymers with unique physical, chemical, and biological features. However, the lack of intrinsic antibacterial property of native BC limits its broad biomedical applications where such property is highly required to prevent contamination or infection caused by attached bacteria. In this work, we developed a simple and facile method to fabricate a dual-functional BC membrane by physical incorporation of gold nanorods (GNRs) followed by deposition of a phase-transitioned bovine serum albumin (PTB) film. Due to the broad-spectrum antifouling property of the PTB film, the resulting membrane could prevent the adhesion and accumulation of bacteria. A few bacteria that broke through the protection of the PTB film could be eradicated under short-term irradiation of a near-infrared laser due to the excellent photothermal property of incorporated GNRs. The whole fabrication was conducted in a simple and environmentally friendly manner, avoiding complicated processes and toxic organic solvents. Moreover, because all the components were biocompatible, the resulting membrane showed negligible cytotoxicity in vitro and good histocompatibility in vivo . This work thus provided a reliable way to endow BC with antibacterial property, being beneficial for diverse biomedical applications.